1982
DOI: 10.4141/cjps82-105
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Estimating Yield Loss of Barley Due to Canada Thistle

Abstract: Research Stution, A,qriculture Cunudu, Lucombe, Alberta T)C 150. Contribution ntt.423, reteivetl I0 Apr. l9Bl, uctepred 23 Feb. 1982. O'Sur-r-rvnN, P. A., Kossrrz,V. C., Wtrss

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 2 publications
1
42
2
Order By: Relevance
“…Overall, the empirical strengths (i.e., r 2 ) of the yield loss relationships in this study were lower than that reported for annual cropland by O'Sullivan et al (1982O'Sullivan et al ( , 1985 and Moyer et al (1991) in Alberta. However, the forementioned studies were conducted within cultivated, (NS) or significantly different at P Ͻ 0.10 (*), P Ͻ 0.05 (**), or P Ͻ 0.01 (***).…”
Section: Resultscontrasting
confidence: 78%
“…Overall, the empirical strengths (i.e., r 2 ) of the yield loss relationships in this study were lower than that reported for annual cropland by O'Sullivan et al (1982O'Sullivan et al ( , 1985 and Moyer et al (1991) in Alberta. However, the forementioned studies were conducted within cultivated, (NS) or significantly different at P Ͻ 0.10 (*), P Ͻ 0.05 (**), or P Ͻ 0.01 (***).…”
Section: Resultscontrasting
confidence: 78%
“…In 1994 and 1996, Canada thistle dry weight tended to be higher in the barley/canola than the canola/barley rotation. This was most evident where no in-crop herbicide was applied, and was likely due to the superior competitiveness of barley compared with canola (O'Sullivan et al 1982(O'Sullivan et al , 1985.…”
Section: In-crop Herbicide Applicationmentioning
confidence: 95%
“…Root expansion has been estimated at 1 cm d -1 , reaching a depth of 1.8 m in 2 yr (Nadeau and Vanden Born 1989). Yield losses due to Canada thistle in barley and canola have been shown to be considerably higher than those caused by equivalent densities of wild oat (Avena fatua L.) (O'Sullivan et al 1982;O'Sullivan et al 1985).…”
mentioning
confidence: 99%
“…1977, Damanakis 1984). It is recognized as a very competitive weed (Hodgson 1968, O’Sullivan et al. 1982, O’Sullivan et al.…”
Section: Introductionmentioning
confidence: 99%